The correlation between socioeconomic status and health self-management in the elderly - Chang-Xiang Chen; Li-Na Feng; Shu-Xing Li (Elsevier, 2014)
Purpose: To determine the correlation between socioeconomic status and health self-management in the elderly and to provide a scientific basis for the promotion of healthy ageing. Methods: We recruited 6173 people aged ≥60 years from three regions in Hebei Province using the multi-stage stratified cluster sampling method. The participants were surveyed using questionnaires. Results: The health self-management behaviours of elderly people differed with the area of residence, education level, and personal monthly income. An ordered probit model showed that behaviours were better in elderly people who lived in urban areas, who were educated to college level or higher, and with higher monthly incomes (p < 0.05). Conclusion: Socioeconomic status plays a decisive role in health self-management in the elderly. We suggest appropriate measures for promoting health self-management among the elderly.